Programming 16-Bit PIC Microcontrollers in C - Learning to Fly the PIC 24 (2nd Edition) - Di Jasio, Lucio (Elsevier, 2012)
Most readers will associate Microchip's name with the ubiquitous 8-bit PIC microcontrollers but it is the new 16-bit PIC24F family that is truly stealing the scene. Orders of magnitude increases of performance, memory size and the rich peripheral set make programming these devices in C a must. This new guide by Microchip insider teaches readers everything they need to know about the architecture of these new chips: How to program them, how to test them, and how to debug them. The author’s common-sense, practical, hands-on approach starts out with basic functions and guides the reader step-by-step through even the most sophisticated programming scenarios. Experienced PIC users, including embedded engineers, programmers, designers, and SW and HW engineers, and new comers alike will benefit from the text’s many thorough examples, which demonstrate how to nimbly sidestep common obstacles and take full advantage of the many new features.